Color vision during pregnancy - Pfohl, Melissa, author; Volbrecht, Vicki J., advisor; Nerger, Janice L., advisor; Laybourn, Paul, committee member; DeLosh, Edward, committee member (Colorado State University. Libraries, 2012)
Color vision deficiencies, both congenital and acquired, are well documented. Acquired color vision deficiencies can arise from a variety of systemic and ocular problems. Previous research has shown that modulation of hormone levels leads to changes in visual perception. Pregnancy involves predictable increases in hormone levels, so this study examined how naturally occurring changes in endogenous levels of steroid hormones during pregnancy may affect color perception and visual acuity. Color vision testing was conducted at regular time intervals over the duration of pregnancy for 6 women as well as a control group of non-pregnant, non-contraceptive using women. As levels of hormones increased over the course of pregnancy, error scores were predicted to increase, indicating increasing losses in color perception. No significant differences were found between pregnant and control participants for any of the color vision tests conducted across any of the time periods tested; however, four of the pregnant participants did show increases in error scores in the shorter wavelengths as time elapsed. The lack of significant differences could indicate that there are compensatory mechanisms for the body to adjust to increasing levels of endogenous hormones from pregnancy. This study has opened up myriad possibilities for future research examining the relationship of hormones and neurosteroids and their effects on color vision.
Keywords: color vision; pregnancy